Working with and for Animals: Getting the Theoretical Framework Right. Issue 1 (2nd January 2018) - Nussbaum, Martha C.
Abstract : Two common approaches to the ethics of animal welfare are profoundly defective. One, an anthropocentric approach that orders forms of life by their likeness to human life, fails to grasp the variety and complexity of animal lives. A second, the Utilitarian approach, does better by seeing that pain is ubiquitously bad, but it does not articulate the diverse ways in which animal lives can be thwarted. I argue that a version of the Capabilities approach does much better, directing law and policy well. I develop this approach and confront it with a number of difficult questions.